Anti-interleukin 5 therapies failure criteria in severe asthma: a Delphi-consensus study. (October 2021) - Mattei, Laura; Suehs, Carey M.; Alagha, Khuder; Bourdin, Arnaud; Brousse, Christophe; Charriot, Jeremy; Devouassoux, Gilles; Fry, Stephanie; Guilleminault, Laurent; Gouitaa, Marion; Taille, Camille; Chanez, Pascal; et al.
Background: Current practices for assessing response to anti-interleukin 5/R treatment in severe asthma patients are heterogeneous. The objective of this study was to achieve an expert consensus defining failure criteria for anti-interleukin 5/R treatment in severe asthma patients. Methods: Experts were invited to a 5-round Delphi exercise if they were pulmonologists managing ⩾30 patients at a nationally recognized severe asthma expert centre. Following two rounds of statement-generating brainstorming, the expert panel ranked each statement according to a 5-point Likert-type scale during three additional rounds. Positive consensus was considered achieved when ⩾80% of experts agreed with a statement with >50% strong agreement and <15% disagreement. Results: Twenty experts participated in the study. All experts agreed that predefined treatment goals defining effectiveness should be personalized during shared decision making via a patient contract. Treatment failure was defined as (1) absence of a reduction in exacerbation rates by ⩾25% or (2) absence of a reduction in oral corticosteroid therapy by ⩾25% of the initial dosage or (3) occurrence of emergency room visits or hospitalizations after 6 months of treatment. Treatment failure should result in discontinuation. For partial responders, treatment discontinuation was not recommended unless an alternative from another therapeutic class exists and should be discussed in a multidisciplinary consultation. Conclusion: The present study provides objective criteria for anti IL5 or IL5R failure in severe asthma and suggests consensus based guidelines for prescription, evaluation and discontinuation decision-making.